EMPOWERMENT OF VILLAGE COMMUNITIES IN THE DEVELOPMENT FRAMEWORK THE UNITARY STATE OF THE REPUBLIC OF INDONESIA - Rukanda, Nandang (IKIP Siliwangi Bandung, 2017)
Empowerment of village communities, must be developed in accordance with the awareness and form of the existing cultural and ecological systems, in order to provide added value to the life of the community itself, and ultimately help the community to realize itself that the development framework leads to the model of building integrity The Unitary State of the Republic of Indonesia.